The Causal Nexus between Renewable Energy, CO2 Emissions, and Economic Growth: New Evidence from CIS Countries - Avazkhodjaev, Salokhiddin; Usmonov, Jaloliddin; Bohdalová, Mária; Lau , Wee-Yeap (International Journal of Energy Economics and Policy, 2022)
This study examines the long-run and short-run of causal nexus between renewable energy generation, CO2 emissions, and economic growth in selected Commonwealth of Independent States (CIS), namely Azerbaijan, Russian Federation, Belarus, Kazakhstan, and Uzbekistan over the period from 2002M01 to 2020M12. The study uses the nonlinear autoregressive distributed lag (NARDL) model to examine the long-run and short-run asymmetric effects between selected variables under concern. The results of empirical model estimation suggested that renewable energy generation has a significant long-run positive effect on CO2 emissions and economic growth in the economies under study, except Kazakhstan. Indeed, renewable energy has an insignificant negative long-run effect on the economic growth in Kazakhstan. Our empirical results summarized that the short-run coefficients of renewable energy generation have a significant steadily positive effect on carbon emission and economic growth in all selected countries under study. Finally, results of the GIRF analysis provided that the innovation shocks оf renewable energy generation have a positive steady-state impact оn CO2 emissions in the economies of CIS countries. For the policy implication, energy policy must be designed with the development of the economy, the development of the environment, and the use of renewable energy sources in the countries in mind. The promotion of renewable energy sources benefits not only the environment but also the economic conditions of the countries. Thus, economic growth is essential to generate the necessary resources for the research and development of renewable energy technologies and related infrastructure.